2018
DOI: 10.3390/ijerph15112584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Grazing Intensities on Soil C, N, and P in an Alpine Meadow on the Qinghai—Tibetan Plateau, China

Abstract: Inappropriate grazing management is one of the most common causes of grassland degradation, and thus, an assessment of soil properties under different grazing intensities is critical for understanding its effects on ecosystem nutrient cycling and for formulating appropriate management strategies. However, the responses of certain main elements, including soil carbon, nitrogen, and phosphorus, to grazing in alpine meadow ecosystems remain insufficiently clarified. Here, we measured carbon, nitrogen, and phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 65 publications
5
20
0
Order By: Relevance
“…Overall, our meta-analysis indicated that grazing significantly reduced SOC, TN, and C: N ratio in alpine grasslands (Fig. 5), which were in accordance with several other studies (Li et al 2018b;Lu et al 2017;Sun et al 2011). This effect might be attributed to the reduction of the quantity of resources returning to soil, especially litter and belowground biomass allocation.…”
Section: Response Of Soil C N and Related Variables To Grazingsupporting
confidence: 91%
“…Overall, our meta-analysis indicated that grazing significantly reduced SOC, TN, and C: N ratio in alpine grasslands (Fig. 5), which were in accordance with several other studies (Li et al 2018b;Lu et al 2017;Sun et al 2011). This effect might be attributed to the reduction of the quantity of resources returning to soil, especially litter and belowground biomass allocation.…”
Section: Response Of Soil C N and Related Variables To Grazingsupporting
confidence: 91%
“…In each site, soil sampling was conducted at five different positions randomly to represent the land configuration (Rannestad and Gessesse, 2020). The soil sample was collected at the depths of 0-10, 10-20, 20-30 cm before being composited (Li et al, 2018). Then, the sample was brought to the laboratory for chemical analysis.…”
Section: Study Locationmentioning
confidence: 99%
“…Without this replacement of carbon by buffel grass, a greater decline in total OC would have occurred. For example, declines in soil OC have been found at sites with low inputs of root biomass (Li et al 2018), which is expected given that root biomass is the main source of carbon input to soil OC (Rasse et al 2005). Indeed, long-term bare fallow sites with nil inputs of organic matter have been found to lose between 21% and 65% of initial soil OC over 36 and 80 years respectively (Barré et al 2010).…”
Section: The Effect Of Land Use Change On Soil Ocmentioning
confidence: 93%